A economia criativa nos municípios periféricos da região Oeste do Paraná - Kuhn, Sérgio Luiz (2014)
This research aims to "analyze the Creative Economy in peripheral municipalities of Paraná". The research was based on the understanding of the creative economy, from its founding father, John Howkins, focused on intangible asset that generates wealth and is the fastest growing economy in the world. Was based on data from secondary sources, bibliographies and especially also by the official as well as on primary data. To this end, these were searched in 20 municipalities with less than 7,000 inhabitants, having as target a purposive sample of 13 leaders, representatives of public-private, institutional and public bodies, totaling 260 respondents. The research instrument was a questionnaire with objective and subjective questions applied in situ and accompanied by an interview. As a result, it was found that approximately 80% of the leaders are male and which is the predominant training graduation. It was found that the counties recorded in the last decade a negative density of 1.7% (1,563 inhabitants). It was noticed that the different stakeholders surveyed believe in the Creative Economy as an alternative socio-economic and cultural development, and should be a structural and design a public-private and institutional policy. Pointing to an average growth of 103.8% of their numerous activities, areas and structures, with the greatest potential for implementation in the short and medium term the newspaper itself, rural and eco tourism, eco parks and travel plans, the vocational and language schools, the municipal theater, recycling and reuse of materials with added value, drawing, painting and others. The áreas of Pato Bragado, Quatro Pontes, Entre Rios do Oeste, Maripá, Mercedes e Serranópolis do Iguaçu are among the top municipalities performers in Creative Economy. However, the 20 studied municipalities need to overcome several bottlenecks difficulty with skilled labor, since they lose workforce of young talent for the regional centers that have higher job creation and greater opportunities for employment, income, studies and others. It has high dependence on agriculture, as well as federal and state public resources, as well as several critical social indicators of GDP, HDI, municipalities dormitories, among others. It is concluded that the Creative Economy through diversification of activities, gathers strength and expertise to leverage the growth and development of the peripheral municipalities, through their main public and private actors, organizations, institutions and citizens, among others.